From Flash Sales to Feelings: The Mediating Role of Positive Emotion in Impulsive buying on TikTok Shop Live Streaming : Survey on Z Generation in Bandung - Rike Nurhayati Azis; Alfitman; Eri Besra (LP2M IAIN Palopo, 2025)
The advancement of digital technology and the rising trend of live streaming in e-commerce have significantly transformed consumer behavior, particularly among Generation Z, who are characterized by impulsive tendencies and high responsiveness to promotional stimuli. In this context, TikTok Shop has emerged as a popular platform offering interactive features such as flash sales and hedonic shopping experiences, both of which can elicit positive emotions and trigger spontaneous purchase decisions (impulsive buying). This study aims to examine the influence of flash sales and hedonic shopping motivation on impulsive buying, with positive emotion as a mediating variable among Generation Z consumers in Bandung City. A quantitative approach with an explanatory research design was employed, using purposive sampling to collect data from 160 respondents who had engaged in impulsive purchases via TikTok Shop live streaming. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique through the SmartPLS 4.0 software. The results reveal that both flash sales and hedonic shopping motivation have a positive and significant influence on positive emotion and impulsive buying. Furthermore, positive emotion is found to partially mediate the relationship between the independent variables and impulsive buying behavior. These findings contribute to the refinement of digital marketing strategies and offer theoretical insights into consumer impulsivity in the digital commerce era.